Effects of arsenic and cadmium on bioaccessibility of lead in spiked soils assessed by Unified BARGE Method. (July 2016) - Xia, Qing; Peng, Cheng; Lamb, Dane; Kader, Mohammed; Mallavarapu, Megharaj; Naidu, Ravi; Ng, Jack C.
Abstract: The bioaccessibility of lead (Pb) in contaminated soils has been extensively studied, including the influence of soil properties on Pb bioaccessibility. However, little is known about the effects of other metals/metalloid, such as arsenic (As), cadmium (Cd) on the bioaccessibility of Pb, i.e. whether As or Cd could increase or decrease the solubility of Pb in human gastrointestinal tract when Pb-contaminated soil and As-contaminated (or Cd-contaminated) soil are ingested simultaneously. Furthermore, it is far from clear that if soil property could make a difference to these effects. In this study, seven types of soils were collected in Australia and spiked with As, Cd or Pb. Gastric bioaccessibility of Pb ranged from 44 ± 0.9% to 100 ± 6.7% whilst intestinal bioaccessibility dropped to 1 ± 0.2% to 36 ± 1.7%. Statistical analysis shows total Pb in soil was the most significant controller for bioaccessible Pb. Effects of As and Cd on the bioaccessibility of Pb in simulated human digestive system were studied by mixing As-spiked soil (or Cd-spiked soil) with Pb-spiked soil of the same type during bioaccessibility test. Results reveal that neither As nor Cd had impact on Pb bioaccessibility, which indicates when As, Cd and Pb aged in soils separately, they may behave independently in the bioaccessibility measuring system. This finding can be part of evidence to assume additive effect when it comes to estimate the bioaccessibility of mixtures of independently-aged As and Pb (or Cd and Pb) in soils. Highlights: Total Pb concentration in soil was the most important variable for bioaccessible Pb. No interaction was observed between Pb and As (or Cd) during bioaccessibility test. Addition of elemental effect may apply when spiked soils are aged independently.